The Ebola outbreak, 2013–2016: old lessons for new epidemics. (10th April 2017) - Coltart, Cordelia E. M.; Lindsey, Benjamin; Ghinai, Isaac; Johnson, Anne M.; Heymann, David L.
Abstract : Ebola virus causes a severe haemorrhagic fever in humans with high case fatality and significant epidemic potential. The 2013–2016 outbreak in West Africa was unprecedented in scale, being larger than all previous outbreaks combined, with 28 646 reported cases and 11 323 reported deaths. It was also unique in its geographical distribution and multicountry spread. It is vital that the lessons learned from the world's largest Ebola outbreak are not lost. This article aims to provide a detailed description of the evolution of the outbreak. We contextualize this outbreak in relation to previous Ebola outbreaks and outline the theories regarding its origins and emergence. The outbreak is described by country, in chronological order, including epidemiological parameters and implementation of outbreak containment strategies. We then summarize the factors that led to rapid and extensive propagation, as well as highlight the key successes, failures and lessons learned from this outbreak and the response. This article is part of the themed issue 'The 2013–2016 West African Ebola epidemic: data, decision-making and disease control'.